Trends and Gender Disparities in Grades and Grade Anomalies among Bioscience and Health-Related Major Students before, during, and after COVID-19 Remote Instruction - Alysa Malespina; Fargol Seifollahi; Chandralekha Singh (MDPI AG, 2024)
In this study, we investigate student performance using grades and "grade anomalies" across periods before, during, and after COVID-19 remote instruction in courses for bioscience and health-related majors. Additionally, we explore gender equity in these courses using these measures. We define grade anomaly as the difference between a student's grade in a course of interest and their overall grade point average (GPA) across all other courses taken up to that point. If a student's grade in a course is lower than their GPA in all other courses, we refer to this as a "grade penalty". Students received grade penalties in all courses studied, consisting of twelve courses taken by the majority of bioscience and health-related majors. Overall, we found that both grades and grade penalties improved during remote instruction but deteriorated after remote instruction. Additionally, we find more pronounced gender differences in grade anomalies than in grades. We hypothesize that women's decisions to pursue STEM careers may be more influenced by the grade penalties they receive in required science courses than men's, as women tend to experience larger penalties across all periods studied. Furthermore, institutions concerned with equity should consider grade penalties as a straightforward measure and make a conscious effort to consider their implications.